The wealth effect of forced bank mergers and cronyism - Chong, Beng-Soon; Liu, Ming-Hua; Tan, Kok-Hui (Journal of Banking & Finance, 2006)
This study examines the impact of forced bank mergers on the shareholders’ wealth of Malaysian banks. Forced bank mergers, which are the result of direct government intervention in the consolidation of the banking industry, are generally rare. Unlike the findings on voluntary mergers and acquisitions, our study shows that the forced merger scheme destroys economic value in aggregate and the acquiring banks tend to gain at the expense of the target banks. Further analysis shows that the contrasting forced merger finding is linked to cronyism.